W. A. Blountet al. (Editors), The Revised Statutes of the State of Florida 782–83 (1892), tit. 2, art. 5, § 2425 - (:unkn) unknown (General Publisher, 1868)
Prohibited the manufacture or sale of slungshots or metallic knuckles. Punishable by imprisonment for up to 6 months or a fine up to $100.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS